A Rare Diagnosis in an Infant with Upper Airway Obstruction: Lymphangioma - Nagehan Aslan; Didar Arslan; Özden Özgür Horoz; Bilen Onan; Muhammed Dağkıran; Özgür Sürmelioğlu; Dinçer Yıldızdaş (Galenos Yayinevi, 2017)
Lymphangiomas, or cystic hygromas, are relatively uncommon congenital malformations of the lymphatic system that usually diagnosed during the neonatal period and usually localized in the head and neck. Surgery is the first-line treatment of lymphangiomas, however, surgery can be challenging due to the close relationship between the cysts and important neurovascular structures at anatomic neighborhood and high recurrence potential. Among the alternative therapies, sclerotherapy has been at the forefront in recent years. In this paper, we report a case of a patient, who was referred with sudden respiratory distress and underwent emergency tracheostomy, and discuss lymphangiomas and treatment options in the light of the literature.